Postbiotic-Enabled Targeting of the Host-Microbiota-Pathogen Interface: Hints of Antibiotic Decline? - Matteo Puccetti; Styliani Xiroudaki; Maurizio Ricci; Stefano Giovagnoli (MDPI AG, 2020)
Mismanagement of bacterial infection therapies has undermined the reliability and efficacy of antibiotic treatments, producing a profound crisis of the antibiotic drug market. It is by now clear that tackling deadly infections demands novel strategies not only based on the mere toxicity of anti-infective compounds. Host-directed therapies have been the first example as novel treatments with alternate success. Nevertheless, recent advances in the human microbiome research have provided evidence that compounds produced by the microbial metabolism, namely postbiotics, can have significant impact on human health. Such compounds target the host-microbe-pathogen interface rescuing biotic and immune unbalances as well as inflammation, thus providing novel therapeutic opportunities. This work discusses critically, through literature review and personal contributions, these novel nonantibiotic treatment strategies for infectious disease management and resistance prevention, which could represent a paradigm change rocking the foundation of current antibiotic therapy tenets.